Synthesis and Characterization of Cerium(IV) Arsenomolybdate Cationic Exchanger - Teena; Kumar, Virendra; Shukla, I.C.; Khanna, Neena (Asian Journal of Chemistry, 2017)
In present work, three component inorganic ion exchanger of an H+ form of cerium(IV) arsenomolybdate has been synthesized by mixing solution of ceric ammonium nitrate (0.1 M) with sodium arsenate solution (0.1 M) and sodium molybdate solution (0.1 M) in different volume ratios to get different samples. One of the samples was selected on the basis of high ion-exchange capacity as determined by column method. The ion-exchange capacity of the material for Na+ has been found to be 0.98 meq/g of the exchanger. The material has been characterized on the basis of pH titration, thermal and chemical stabilities, FTIR, TGA, X-ray and SEM studies. The scanning electron microscopy of the material shows a regular diamond shape morphology. Chemical stability of the exchanger was checked in various acidic and basic media. Binary separations of some important metal ion pairs were achieved.